Lettuce in an economic plot integrated to the irrigation system cuca de umbu in the municipality of Salgueiro, Pernambuco, Brazil - Leite, Daniel de Carvalho; Teles, Elton Carlos Pereira Vieira de Alencar; Arraes, Francisco Dirceu Duarte; Alves, Jânio Eduardo de Araújo (Revista Verde de Agroecologia e Desenvolvimento Sustentável, 2019)
The irrigation system, called umbu cuca, can be an efficient and advantageous alternative for the family farmers in the production of lettuce in economical land. The aim of this study was to evaluate the lettuce production at the economic site integrated to the umbu cuca irrigation system with the conventional irrigated manure with irrigation system in the municipality of Salgueiro, Pernambuco, Brazil. The experiment consisted of two treatments, economical and conventional with four replications, the average number of leaves per plant was evaluated; mean height of seedlings; diameter of plant and stem; fresh and dry mass of shoot and root; root length; and water use efficiency. After collection, the data were submitted to the test with 5% probability. The water use efficiency was 2.92% higher for conventional beds, but with the exception of root length that was 2.19 cm larger in conventional beds, all other variables showed that the production was better for the beds with a significant difference for the fresh mass of the plants, which was 103,430 g / greater plant in the economic beds, plant height 3,81 cm, the diameter stem 0.19 cm.